Selekcja informacji w mediach w oparciu o teorię Agendy Setting (Conversatoria Linguistica, 2019)
Article describes the usage of Agenda Setting in a process of creating informational materials in mass media. It shows mechanisms and concessionary factors affecting the hierarchization of information in media such as the way of financing, concessionary records, market’s requirements or human factor, meaning publisher or the editor in chief. The text is trying to describe relationship between hierarchization of information and gatekeeping and mediation. It also talks about giving contexts to information, so called framing in professional literature. Agenda Setting and selection and placement of the news with broadcasting institutions were also described in the text. There was emphasis put on meaning of journalist ethic and manipulation processes in publishing mass broadcasts.